Terrain Point Cloud data of a Deep-Sea Cliff offshore Greenland and the Associated Epibenthic Fauna - Loïc Van Audenhaege; Emmeline Broad; Katharine R Hendry; Veerle A I Huvenne (PANGAEA, 2021)
Terrain data retrieved with a forward-looking sonar (Reson7125) the ROV Isis (NOC, UK) used to map a deep-sea wall located offshore the West coast of Greenland (Labrador Sea, [63°51.9 extquotesingleN, 53°16.9 extquotesingleW, depth: 703 to 803 m]) with a high resolution. The file contains a 3D point cloud storing terrain variables derived from the bathymetry [m] and backscatter [nominal unit] extracted at a resolution of 0.3 m. Different terrain descriptors were computed: Slope, Bathymetric Position Index (BPI), Terrain Ruggedness Index, Roughness, Mean and Gaussian curvatures and orientations (Northness and Eastness), at scales of 0.9, 3 and 9 m. Using a Principal Component Analysis (PCA), the terrain descriptors enabled to retrieve 4 terrain clusters and their associated confusion index, to investigate the spatial heterogeneity of the terrain.
In: Van Audenhaege, L et al. (2021): High-Resolution Vertical Terrain of a Deep-Sea Cliff offshore Greenland and the Associated Epibenthic Fauna [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.931687